Змістові та процесуальні засади взаємодії основних суб’єктів Болонського процесу - Улановська, Анна (Studies in Comparative Education, 2015)
У статті схарактеризовано цілі, завдання та напрямки діяльності основних наднаціональних суб’єктів управління Болонським процесом, які, об’єднавшись у групу Є-4, представляють інтереси провідних стейкхолдерів у галузі вищої освіти. Визначено форми та основоположні принципи їхньої взаємодії у процесі розбудови європейського простору вищої освіти. Досліджено сфери та методи впливу Європейської комісії у контексті модернізації освітніх систем країн-членів Болонського клубу. В статье представлена характеристика целей, задач и направлений деятельности основных наднациональных субъектов управления Болонским процессом, представляющих интересы ведущих стейкхолдеров в области высшего образования. Исследованы формы их взаимодействия в процессе развития Европейского пространства высшего образования. Основополагающими принципами кооперации субъектов Болонского процесса определено единство и согласованность, ориентация на процесс, результат и оценку результатов, постоянство информационного обмена, прозрачность принятия решений, делегирования полномочий. Особое внимание уделено исследованию сфер и методов воздействия Европейской Комиссии в контексте модернизации образовательной системы. An important characteristic of the Bologna process is the multiplicity of interacting stakeholders. The procedure of higher education (HE) policy production is realized in close cooperation between various actors operating at different levels (global, European, national, institutional). This factor promotes the formation of a new multi-level and multi-actor European Higher Education Area (EHEA) and requires detailed analysis. In this article we characterize main goals, objectives and activities of major Bologna supranational subjects, who represent different stakeholder groups in HE: the European University Association, the European Association of Higher Education Institutions, the European Association of Quality Assurance and the European Students’ Union. These pan-European representative organizations united in E-4 Group have become influential consultative members of the Bologna Follow-up Group which oversees the process and monitors the results between the Ministerial conferences. To the main forms of their interaction in the Bologna context we refer: participation in joint projects and studies, conferences, seminars, forums and, of course, cooperation within BFUG. The theoretical analysis of research studies and documents allows to define fundamental principles of the Bologna actors’ interaction. It was found that each organization as a representative structure aims at protecting the interests of a particular group of HE stakeholders united by a common goal – the development of high-quality competitive EHEA. Besides, the need to consolidate efforts in order to achieve strategic goals was accentuated in all Bologna Communiqués and Declarations. Therefore, an important principle of cooperation between major Bologna subjects in the context of HE modernization is unity and coherence. Since the major tasks of BFUG is to organize work of the BP executive structures, achieve the goals through the implementation of key initiatives and monitor results of the modernization process, the next important principle of supranational cooperation, in our opinion, is targeting the process, results, and evaluation of the outcomes. Furthermore, the fundamental principle which is essential for successful cooperation is the sustainability of information exchange. The flow of both formal and informal information among pan-European collective subjects is definitely more internationalized and stable than in other levels of BP. It is also clear that an important condition for the development of a new democratic model of European HE is open governance systems and a free access for all stakeholders. Thus, transparency of a decision-making process is also a crucial principle for BP subjects. Finally, the principle of authority delegation was identified as an integral activity aspect of studied organizations as well as their interaction within the E-4 group, BFUG and joint projects. Special attention in the article is paid to the role the European Commission has in the context of HE modernization. Main areas and methods of its influence are investigated and it is argued that this powerful institution obtains a front position in the BP.